Western Anatolia before Troy proto-urbanisation in the 4th millennium BC? : proceedings of the International Symposium held at the Kunsthistorisches Museum Wien, Vienna, Austria, 21-24 November, 2012 - Horejs, Barbara 1976- (Austrian Academy of Sciences Press, 2014)
"OREA 1 presents the scientific results of the international symposium Western Anatolia before Troy--Proto-Urbanisation in the 4th Millennium BC? The sparse archaeological data published for the 5th and 4th millennia BC and the archaeological picture of western Anatolia, fundamentally changed in the last decades, needed to bring together specialists of western Turkey and the neighbouring regions to discuss new data in the light of socio-cultural processes in the period before Troy. Furthermore, following the results of the ERC research group (ERC project Prehistoric Anatolia), it appeared high time to focus on this period as it had been frequently neglected in the recent dynamic prehistoric research in western Turkey. The intermediate millennia between the archaeological focus on the Neolithic (and early Chalcolithic) of the 7th and 6th millennia BC with ground-breaking results and publications on the one hand and traditional research on the Early Bronze Age in the 3rd millennium BC with new input from important key sites on the other hand remained more or less neglected. The symposium aimed to shed light on these developments and focus in particular on the formation of centres of regional and supra-regional importance that emerged in western Anatolia and the broader geographical context of the Balkans, the Marmara Sea, the Greek mainland and Crete"--
Proceedings of an international conference held at the Kunsthistorisches Museum Wien, November 21-24, 2012
Keywords: Geschichte 4000 v. Chr.-3000 v. Chr.; Urbanization / Turkey / History / To 1500 / Congresses; Excavations (Archaeology) / Turkey / Congresses; Cities and towns, Ancient / Turkey / History / Congresses; Antiquities; Cities and towns, Ancient; Excavations (Archaeology); Urbanization; Funde; Geschichte; Verstädterung; Siedlung; Stadt; Turkey / Antiquities / Congresses; Turkey; Türkei; Westanatolien; Konferenzschrift; Konferenzschrift -- 21.-24.11.2012 -- Wien